Evolución histórica de la oralidad y la escritura en el proceso civil español y ecuatoriano - Álvaro Mejía Salazar (Universidad Hemisferios, 2017)
Ecuador faces its greatest challenge in the history of its non-criminal justice administration: the implementation of the judgment by hearing process. Beyond the debate regarding the weaknesses that, in practice, this implementation experiences, it is convenient to make a retrospective review of the history of writing and orality in the processes. To these effects, the evolution of these forms of communication of the procedural acts will be studied; starting from the old age, through the medieval times, to the colonial, republican and contemporary times of the Ecuador. This will lead us to better understand each method of communication of procedural acts and will confirm the convenience of the oral technique—at least as far as the civil process is concerned. The study follow an historic method that analyze all periods of procedural evolution chronologically. This essay will cover a period between primitive societies and the COGEP (the current non-criminal procedural code).